2023
DOI: 10.1002/mabi.202300226
|View full text |Cite
|
Sign up to set email alerts
|

Aminosilane Functionalized Aligned Fiber PCL Scaffolds for Peripheral Nerve Repair

Abstract: Silane modification is a simple and cost‐effective tool to modify existing biomaterials for tissue engineering applications. Aminosilane layer deposition has previously been shown to control NG108‐15 neuronal cell and primary Schwann cell adhesion and differentiation by controlling deposition of ─NH2 groups at the submicron scale across the entirety of a surface by varying silane chain length. This is the first study toreport depositing 11‐aminoundecyltriethoxysilane (CL11) onto aligned Polycaprolactone (PCL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Indeed, the XPS results obtained in the present study showed consistency with what is found in the literature concerning the chemical elemental distribution on the surface upon AUTES silanization. 39,41 However, XPS survey analysis revealed a different chemical composition after Alk-Phtha deposition, although after deprotection, the resulting molecule (Alk-NH 2 ) has the same chemical structure as AUTES. The observed differences were particularly pronounced in the highresolution spectra, with AUTES showing a higher concen-tration on the surface than Alk-NH 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the XPS results obtained in the present study showed consistency with what is found in the literature concerning the chemical elemental distribution on the surface upon AUTES silanization. 39,41 However, XPS survey analysis revealed a different chemical composition after Alk-Phtha deposition, although after deprotection, the resulting molecule (Alk-NH 2 ) has the same chemical structure as AUTES. The observed differences were particularly pronounced in the highresolution spectra, with AUTES showing a higher concen-tration on the surface than Alk-NH 2 .…”
Section: Discussionmentioning
confidence: 99%
“…40 However, Taylor et al reported contrasting results, noting enhanced support for cell adhesion, proliferation, and viability on plain glass coverslips modified with AUTES, thereby introducing a conflicting perspective in the literature. 41 Previous studies have addressed the relationship between diverse chain lengths of aminosilanes and the behavior of human mesenchymal stem cells. Chen et al carried out an investigation focused on elucidating the influence of C 3 and C 11 alkyl chain length in silane molecules, specifically assessing the modified deposition pattern of NH 2 groups on the substrate surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation